Bosna i Hercegovina u procesu integracije u Evropsku uniju / Bosnia and Herzegovina in the EU Integration Process - Pejanović, Mirko (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
A review of the book by Hoda Dedić, PhD, Bosnia and Herzegovina and European Union - prerequisites and achievements of the integration (Bosanska rijeĉ, Tuzla, 2015).